2011
DOI: 10.1002/pssc.201000916
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of T‐gate AlGaN/GaN HEMTs

Abstract: For the first time, we report on degradation mechanisms of short gate length (Lg = 0.15 µm) T‐gate AlGaN/GaN HEMTs, and compare to previously reported findings for GaN field plate devices of the same gate length. Both types of studied devices were subjected to temperature‐stress tests in air. T‐gate devices were stressed with a drain bias of 15 V, while field plate devices were stressed with a drain bias of 30 V. Some T‐gate devices were also stressed in dry nitrogen to observe any impact of the environment. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…When stressing occurs in N 2 ambients, this reaction manifests itself as ''sinking'' whereby the Ni layer appears to diffuse down and consume the underlying AlGaN layer and make electrical contact to the 2DEG. However, when stressing occurs in O 2 or air, the O 2 present reacts with the Ni/AlGaN mixture to form an oxidized Ni phase as confirmed using HAADF-STEM combined with electron energy loss spectroscopy [23].…”
Section: Introductionmentioning
confidence: 95%
“…When stressing occurs in N 2 ambients, this reaction manifests itself as ''sinking'' whereby the Ni layer appears to diffuse down and consume the underlying AlGaN layer and make electrical contact to the 2DEG. However, when stressing occurs in O 2 or air, the O 2 present reacts with the Ni/AlGaN mixture to form an oxidized Ni phase as confirmed using HAADF-STEM combined with electron energy loss spectroscopy [23].…”
Section: Introductionmentioning
confidence: 95%
“…However, the reliability issues of these devices are not yet fully understood and hence attract significant research effort. In particular, the off-state degradation of AlGaN/GaN HEMTs has recently been intensively studied 2,3,4,5,6,7,8,9,10,11,12,13,14 . It is now well known that when a negative bias is applied to the gate electrode of these devices, the gate current, I g , eventually starts to increase progressively.…”
mentioning
confidence: 99%
“…It is now well known that when a negative bias is applied to the gate electrode of these devices, the gate current, I g , eventually starts to increase progressively. This degradation is accompanied by the appearance of electroluminescence (EL) hot spots next to the drain side edge of the gate metal 3,4,5,9 , and by the physical degradation of the semiconductor in the form of pits and grooves on the device surface 4,5,6,7,8,10,11,12 . However, it is still not clearly established what the mechanism is that triggers this type of degradation, and also why this degradation takes place in such a spatially localized fashion.…”
mentioning
confidence: 99%
“…Previous work has suggested that defects and reactions occur where the electric field is largest in a HEMT, at the gate edges. 20,26 However, in this case, due to this large, nearly symmetric electric/strain field present, it is possible that the fields influence the diffusion or reactivity of the layers and O directly contributing to the morphology of the defect and explain the similarity between the defect shape and the simulated electric/strain field contours. This could indicate that it is the shape of the electric/strain field itself that influences the defect morphology and not just the large magnitude of the field for HEMTs with L G < 100 nm.…”
Section: -2mentioning
confidence: 93%